VHDL modeling of fuzzy wavelet based handwritten recognition system - Pang, W. L.; Reaz, Mamun Ibn; Ibrahimy, Muhammad Ibn; Low, L. C.; Mohd-Yasin, Faisal; Rahim, R. A. (2006)
The handwritten character recognition system usi ng fuzzy wavelet is modelled using Very High Speed Hardware Description Language (VHDL). The fu zzy wavelet handwritten recognition is a system based on human perception. The time-frequency localization cap abilities of wavelet transform in feature extraction enhances the accuracy of recognition at pixel level. The characteristic features of handwritten character in image format are extracted by taking Haar wavelet transf orm. The design was implemented using VHDL. The VHDL model is simulated and synthesized using Altera’s Quartus II. The system operates up to 13.27 Mega Hertz (MHz) with equivalent longest propagation delay of 75.336ns.